Faktor Penghambat Penyaluran Bantuan Langsung Tunai Melalui Dana Desa Pada Masa Pandemi Covid-19 di Desa Iloheluma - Dewy Fadlun Alhasni; Usan Bagou; Tety Thalib; Jamaluddin Arifin (Equilibrium: Jurnal Pendidikan, 2023)
Abstract. Abstract. This study aims to determine the inhibiting factors for the distribution of direct cash assistance through village funds during the Covid-19 pandemic in Iloheluma Village. With research sub-focus namely budget limitations, budget delays, reference criteria for prospective recipients. This research uses a qualitative descriptive research type. Data collection techniques used are observation techniques, interviews and secondary data recording. In accordance with the type of research used, the data analysis technique used is a qualitative analysis technique. The results of the study show that, seen from the aspect of Budget Availability, it hinders. Because the available funds or budget are limited or insufficient to be distributed as a whole to the poor in the first year, namely 2020, so that in 2020 direct cash assistance through the Village Fund will be distributed to only 35 families out of 158 families of the poor in Iloheluma Village, Posigadan District. Viewed from the aspect of Budget Delays hampering, because the budget or Village Funds were late in entering the Village Cash Account of the Iloheluma Village Government through the Regional General Cash Account, this had an impact on the distribution of Village Fund Direct Cash Assistance (BLT) to the poor who were affected by the pandemic or Covid-19 in Iloheluma Village experienced delays. Judging from the factors that hinder the Recipient Candidate Criteria Reference Standards. Because the reference criteria for potential recipients of Village Fund Direct Cash Assistance are unclear, so the village government in determining potential recipients, in the context of distributing Village Fund Direct Cash Assistance only refers to data on the list of poor people in Iloheluma Village. research on the Inhibiting Factors for the Distribution of Direct Cash Assistance through Village Funds during the Covid-19 Pandemic Period as seen from the factors of budget availability, budget delays, and standard reference criteria for prospective recipients hindering the distribution of Village Fund Direct Cash Assistance in Iloheluma Village.Keywords: Inhibiting Factors, Distribution, Direct Cash Assistance, Village Funds, Covid-19 PandemicAbstrak. Penelitian ini bertujuan untuk mengetahui Faktor-Faktor Penghambat Penyaluran Bantuan Langsung Tunai Melalui Dana Desa pada Masa Pandemi Covid-19 di Desa Iloheluma. Dengan sub fokus penelitian yaitu Keterbatasan anggaran, keterlambatan anggaran, acuan kriteria calon penerima. Penelitian ini menggunakan jenis penelitian deskriptif kualitatif. Teknik pengumpulan data yang digunakan adalah Teknik Observasi, Wawancara dan pencatatan data sekunder. Sesuai dengan jenis penelitian yang digunakan, maka teknik analisis data yang digunakan adalah teknik analisis kualitatif. Hasil penelitian menunjukan bahwa, dilihat dari aspek Ketersediaan Anggaran menghambat. Karena Dana atau anggaran yang tersedia terbatas atau tidak mencukupi dibagikan secara keseluruhan kepada masyarakat miskin pada tahun pertama yaitu tahun 2020, sehingga pada tahun 2020 tersebut Bantuan langsung Tunai melalui Dana Desa yang disalurkan baru 35 kk dari 158 kk masyarakat miskin di Desa iloheluma Kecamatan Posigadan. Dilihat dari aspek Keterlambatan Anggaran menghambat, karena anggaran atau Dana Desa terlambat masuk Rekening Kas Desa Pemerintah Desa Iloheluma melalui Rekening Kas Umum Daerah, hal ini berdampak pada penyaluran Bantuan Langsung Tunai (BLT) Dana Desa kepada masyarakat miskin yang terdampak pandemi atau Covid-19 di Desa Iloheluma mengalami keterlambatan. Dilihat dari faktor Standar Acuan Kriteria Calon Penerima menghambat. Karena acuan kriteria calon penerima Bantuan Langsung Tunai Dana Desa kurang jelas, sehingga pemerintah desa dalam menentukan calon penerima, dalam rangka penyaluran Bantuan Langsung Tunai Dana Desa hanya mengacu pada data daftar warga miskin yang ada di Desa Iloheluma. Secara keseluruahn penelitian mengenai Faktor-Faktor Penghambat Penyaluran Bantuan Langsung Tunai Melalui Dana Desa pada Masa Pandemi Covid-19 yang dilihat dari faktor ketersediaan anggaran, keterlambatan anggaran, dan standar acuan kriteria calon penerima menghambat penyaluran Bantuan Langsung Tunai Dana Desa di Desa Iloheluma.